The The benefits of "Academic Writing" course for the freshmen in English-medium-instruction departments in a Turkish state university - Burak Tomak (Istanbul Kültür University, 2022)
The importance of academic writing is prevalent especially for the students taking English-medium instruction (EMI). After the intensive language lessons in the School of Foreign Languages, students must reach a certain level (B2) in order to pursue their academic studies in English. In addition to their departmental courses, freshmen in some EMI departments are offered "Academic Writing" course while some others do not have this opportunity. Thus, this study has tried to determine the efficiency and the benefits of this course for the freshmen in this university. For the purpose of the study, 5 freshmen that took "Academic Writing" course in the spring semester and 6 other freshmen who were not offered this course were assigned to write an academic essay on a given topic by the researcher. After the submission of their papers, the researcher had semi-structured interviews with each participant. Data were analyzed qualitatively via manual coding. It was found that the students who took "Academic Writing" course were more successful than their peers who were not given this opportunity in terms of grammar and vocabulary knowledge as well as the content formation in their academic papers.